Pengaruh Gratis Ongkos Kirim, Potongan Harga, Iklan, Flash Sale, dan Cashback terhadap Minat Beli Konsumen Shopee di Surabaya - Novadinastia , Faiza Aulia; Rusdianto, R. Yuniardi (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effects of free shipping, discounts, advertising, flash sales, and cashback on purchase intention among Shopee consumers in Surabaya. Using a quantitative approach, data were collected from 160 respondents selected through purposive sampling via an online questionnaire and analyzed using SPSS. The results show that independent variables simultaneously have a significant effect on purchase intention. Partially, discounts, advertising, and cashback significantly influence purchase intention, while free shipping and flash sales have no significant effect. These findings highlight the strategic role of selected promotional tools in strengthening consumer purchase intention. Keywords: Free Shipping; Discounts; Advertising; Flash Sale; Cashback; Purchase Intention